2011
DOI: 10.1016/j.cbpa.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Iron chaperones for mitochondrial Fe–S cluster biosynthesis and ferritin iron storage

Abstract: Protein controlled iron homeostasis is essential for maintaining appropriate levels and availability of metal within cells. Recently, two iron chaperones have been discovered that direct metal within two unique pathways: (1) mitochondrial iron–sulfur (Fe–S) cluster assembly and (2) within the ferritin iron storage system. Although structural and functional details describing how these iron chaperones operate are emerging, both share similar iron binding affinities and metal–ligand site structures that enable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…However, while PCBPs 1-3 can directly bind ferritin, PCBP4 appears to act indirectly, perhaps as an intracellular iron buffer for the other PCBPs [8,31]. Indeed, iron-loaded PCBP1 is able to bind to ferritin in vivo and in vitro in multiple molar equivalents with low micromolar affinity, as was determined from isothermal titration calorimetric studies [31,36]. This binding affinity of iron-PCBP1 for ferritin is much higher than the binding affinity of iron(II) for ferritin or the affinity of apo-PBCP1 for ferritin [31,35].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 2 more Smart Citations
“…However, while PCBPs 1-3 can directly bind ferritin, PCBP4 appears to act indirectly, perhaps as an intracellular iron buffer for the other PCBPs [8,31]. Indeed, iron-loaded PCBP1 is able to bind to ferritin in vivo and in vitro in multiple molar equivalents with low micromolar affinity, as was determined from isothermal titration calorimetric studies [31,36]. This binding affinity of iron-PCBP1 for ferritin is much higher than the binding affinity of iron(II) for ferritin or the affinity of apo-PBCP1 for ferritin [31,35].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…PCBP 1, and probably PCBP2 [8], appears to be able bind Fe(II) in a six coordinate oxygen/nitrogen ligand environment [36]. PCBP1 can bind a total of three iron atoms, in which the first iron atom has a dissociation constant (K d ) of 0.9 ± 0.1 µM and a mean K d of 5.8 ± 0.3 µM for the remaining two iron atoms [9,32,35].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial evidence for this hypothesis came from findings of decreased ISC-dependent protein activities in FA patients and in yeast and animal models of the disease (54, 314,361,375). Subsequent studies have demonstrated interactions between Fxn and the ISC assembly complex (421). Results with the bacterial Fxn ortholog CyaY demonstrate interactions between CyaY and IscS, the bacterial cysteine desulfurase involved in ISC assembly (256,358,399).…”
Section: Brain Disorders Of Mitochondrial Iron Dyshomeostasismentioning
confidence: 99%
“…The human cysteine desulfurase nitrogen fixation 1 homologue (Nfs1) along with an accessory protein Isd11 serves as sulfur donors for the assembly of ISCs (44, 252, 336). The frataxin (Fxn) protein has been implicated in ISC synthesis in addition to other proposed functions (383,421). ISCs are assembled on the human scaffold protein ISC assembly protein U (IscU), and interactions between IscU, Nfs1, and Isd11 form the core ISC complex, which then interacts with Fxn (387).…”
Section: Fig 11 Transport Of Iron For Mitochondrial Uptakementioning
confidence: 99%